Authorship and musical style in Wes Anderson’s films from the 2010s (Intercom - Brazilian Journal of Communication Sciences, 2024)
In Wes Anderson's films, the music was commonly characterized by pop songs, but Moonrise Kingdom (2012) shows a notable role for the classical music (already present in previous films, even if only as inspiration at times), in addition to consolidating the change of composer from Mark Mothersbaugh to Alexandre Desplat. As indicated by Hrycaj (2013) based on Gorbman (2007), Wes Anderson can be considered a mélomane director, responsible for “auteur music”, with a central role in musical choices. Focusing on Anderson's films from the 2010s, we evaluate changes in stylistic aspects in the use of music, including “montage sequences” and slow motion. As a methodology, we map music in films, film analysis and we use interviews with the director and collaborators.
Keywords: cinema; music; style; Wes Anderson; authorship.